Semiology of graphics: Diagrams, networks, maps - Jacques Bertin (University of Wisconsin Press, 1984)
Originally published in French in 1967, Semiology of Graphics is internationally recognized as a foundational work in the fields of design and cartography. Based on Jacques Bertin's practical experience as a cartographer, part one of this work is an unprecedented attempt to synthesize principles of graphic communication with the logic of standard rules applied to writing and topography. Part two brings Bertin's theory to life, presenting a close study of graphic techniques, including shape, orientation, color, texture, volume, and size, in an array of more than 1,000 maps and diagrams. Now, with a new epilogue written by the author shortly before his death, this new 2010 edition in English reawakens us to the information design possibilities of modern technology. Jacques Bertin was a French cartographer and theorist, and a world renowned authority on the subject of information visualization. In 1954, he founded the Cartographic Laboratory of the Ecole Pratique des Hautes Etudes, and in 1957 he was named director of education. In 1967, Bertin became a professor at the Sorbonne, and in 1974 he was appointed director of education and director of the Geographical Laboratory of the Ecole des Hautes Etudes en Sciences Sociales. In the late 1970s, he became head of research at the Centre National de la Recherche Scientifique.